2014
DOI: 10.20453/renh.v6i2.1795
|View full text |Cite
|
Sign up to set email alerts
|

Factores familiares que influyen en las manifestaciones depresivas en adolescentes del 1.° al 5.° de secundaria de un colegio nacional mixto

Abstract: (40) con severa. La relación factor familiar con tipo de familia y manifestaciones depresivas, hizo ver que el 40,7% (27) pertenece a familias extendidas y presentan manifestaciones depresivas definidas, y el 3,1% (1) de familia monoparental presenta depresión; aunque las diferencias no resultaron significativas (p=0,712). La relación funcionalidad familiar y manifestaciones depresivas mostró que el 50,0% (20) de adolescentes de familias con disfunción severa presentan manifestaciones depresivas bien definidas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 2 publications
0
2
0
Order By: Relevance
“…Participants living with extended families (Table 10) in the current times of COVID-19 do not show significant differences in any of the negative emotional states or family atmosphere dimensions than participants who do not live in extended families. These results they need further exploration because despite the fact that the context where they live is numerous, they do not manifest the problems that could be expected by the greater number of relatives, perhaps as the number of relatives is greater, the students are more likely to establish positive relationships or have more support in the various members of the extended family; differently, the studies by Gonzáles et al 29 when studying family factors and depression in adolescents, show that extended families were mostly dysfunctional and that they were related to depression in adolescents. Further research on this topic is recommended.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…Participants living with extended families (Table 10) in the current times of COVID-19 do not show significant differences in any of the negative emotional states or family atmosphere dimensions than participants who do not live in extended families. These results they need further exploration because despite the fact that the context where they live is numerous, they do not manifest the problems that could be expected by the greater number of relatives, perhaps as the number of relatives is greater, the students are more likely to establish positive relationships or have more support in the various members of the extended family; differently, the studies by Gonzáles et al 29 when studying family factors and depression in adolescents, show that extended families were mostly dysfunctional and that they were related to depression in adolescents. Further research on this topic is recommended.…”
Section: Discussionmentioning
confidence: 90%
“…Research on the family and the presence of psychological or mental health problems have occurred over time, as follows: Pelechano 28 reports that the movement on family therapy and its influence on the presence of psychological problems is important. In Peru, Gonzáles et al 29 found that the majority of families were extended and that most of them functioned in a dysfunctional manner, either to a mild or moderate degree, and that this type of family was related to the depressive symptoms of the adolescents studied; although depressive symptoms were also present in adolescents in single-parent families, these were not statistically significant. Vargas 30 found that before the type of family, it is family functioning that would be significantly related to psychological problems, so when any of its members is altered, it is necessary for the entire family system to be assisted.…”
Section: Family Social Climate and Anxiety Depression And Stressmentioning
confidence: 91%